2022
DOI: 10.1152/jn.00267.2021
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of Rolandic beta rhythm modulation in MEG and EEG

Abstract: The Rolandic beta rhythm, at ~20 Hz, is generated in the somatosensory and motor cortices and is modulated by motor activity and sensory stimuli, causing a short lasting suppression that is followed by a rebound of the beta rhythm. The rebound reflects inhibitory changes in the primary sensorimotor (SMI) cortex, and thus it has been used as a biomarker to follow the recovery of acute stroke patients. The longitudinal stability of beta rhythm modulation is a prerequisite for its use in long-term follow-ups. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 78 publications
2
5
0
Order By: Relevance
“…Beta modulations to active volitional wrist extension and flexion movements have demonstrated high inter-session reproducibility (Espenhahn et al, 2017). In addition, proprioceptive stimulation of the index finger has been shown to elicit highly reproducible induced fields (Illman et al, 2022). Our results are in accordance with these previous results as we also found that both peak beta suppression and rebound amplitudes have excellent reproducibility in the group level, although inter-individual variation may be substantial in the absolute response amplitudes.…”
Section: Reproducibility Of Stimulus Induced Responsessupporting
confidence: 91%
See 3 more Smart Citations
“…Beta modulations to active volitional wrist extension and flexion movements have demonstrated high inter-session reproducibility (Espenhahn et al, 2017). In addition, proprioceptive stimulation of the index finger has been shown to elicit highly reproducible induced fields (Illman et al, 2022). Our results are in accordance with these previous results as we also found that both peak beta suppression and rebound amplitudes have excellent reproducibility in the group level, although inter-individual variation may be substantial in the absolute response amplitudes.…”
Section: Reproducibility Of Stimulus Induced Responsessupporting
confidence: 91%
“…The induced responses appear reproducible irrespective of stimulus modality and frequency band of interest. Good to excellent reproducibility has been reported for frequency modulations (rebound and suppression) at alpha band to a cognitive task (Burgess and Gruzelier, 1996;Vázquez-Marrufo et al, 2017), at beta band to volitional hand movement (Espenhahn et al, 2017) and at beta band to proprioceptive or tactile stimulation of index finger (Illman et al, 2022). Further evidence for the reliability of induced responses is provided by observing the responses to ongoing oscillations (induced steady-state responses).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…was statistically insignificant). βoscillations have been linked to the activity of the primary motor cortex activity as it is well known that somatosensory inputs modulate β oscillations because of motor-cortical mechanisms [56][57][58]. These effects are driven by the ascending projections to M1 [59,60] and by corticocortical connections with the somatosensory cortex [61].…”
Section: Sensorimotor Erd During Tactile Stimulation and Tactile Imagerymentioning
confidence: 99%